Significance of immunohistochemistry and DNA ploidy in differential diagnosis of flat urothelial lesions and conditions using CK20, p53, CD44, ErbB-2, and image cytometry. Issue 1 (July 2016) - Elsayed, Walid S.H.; Abdul-Maksoud, Rehab S.
Abstract : Background: Carcinoma of the urinary bladder is a significant cause of morbidity and mortality. Development of cancer is a process that takes place over many years, sometimes decades, and can be successfully managed if precancer is detected clinically. Urothelial dysplasia and carcinoma in situ (CIS) are related to recurrence and progression of urothelial carcinoma. Distinguishing CIS and dysplasia from reactive atypia is often difficult on the basis of histological features alone. Because this distinction is therapeutically and prognostically critical, confirming the morphologic impression using immunohistochemistry (IHC) is being increasing practiced in routine clinical practice. Aim: We attempted to determine whether an IHC panel would help in this differential diagnosis and the role of DNA ploidy in this aspect. Patients and methods: The ploidy and immunoprofile of 21 cases of CIS and 64 non-CIS conditions (14 urothelial biopsies with dysplasia, 13 biopsies with flat hyperplasia, 16 biopsies with reactive atypia, 11 biopsies with normal urothelium from patients with a history of bladder cancer, and 10 normal ureter sections from nephrectomies) were determined using an image analyzer for ploidy and antibodies against CK20, p53, CD44, and ErbB-2 for IHC. Results: Although the individual specificity of CK20, p53, and ErbB-2 was high (97, 92, and 91%, respectively), their sensitivity for CIS detection was lower, being 79, 80, and 79%, respectively. Whereas 81% of CIS cases showed positivity for at least two of those three markers, only one case of reactive urothelium showed positivity for two of them. The discriminatory performance of CD44 was good, with a sensitivity and specificity for reactive atypia of 100 and 81%, respectively, versus CIS. The DNA aneuploidy was 71% in CIS, 36% in dysplasia, 6% in reactive atypia, and 18% in the normal urothelium of patients with tumors. Conclusion: In conclusion, a panel of CK20, p53, CD44, and ErbB-2 helps to differentiate urothelial CIS from non-neoplastic urothelial atypias. Positive staining for at least two of the three antibodies (CK20, p53, and ErbB-2) is strongly associated with CIS. DNA aneuploidy helps in differentiating CIS from reactive atypia. However, the histologic findings should be a primary determinant in the diagnosis of flat urothelial lesions, with IHC and DNA ploidy playing a supportive confirmatory role.